Jurisprudential analysis of specialized treatments in the State of Ceará (Research, Society and Development, 2024)
The present work aimed to associate the type of legal demand with the procedural characteristics and health care in the municipalities of the State of Ceará. A cross-sectional study of all rulings at the Court of Justice of the State of Ceará was conducted between 2010 and 2018. The data were analyzed descriptively and expressed in absolute frequencies. For the analysis, simple and multiple logistic regression models were constructed between the outcome variable (type of demand Medications/others and ICU beds/surgical procedures) and the independent variables Municipal Human Development Index (HDI-M), ESF coverage and AB, and author of the action. 224 actions were selected for analysis, with the largest demand having the State of Ceará as defendant 147 (65.6%). The city of Fortaleza 153 (68.3%) was the one with the most demands. There was an increase in the number of processes demanding medicines/others until 2015. For processes demanding ICU beds/surgical procedures, an increase in the number over time was noted. There was an association between the IDH-M variable and the type of legal demand. It was concluded that in the state of Ceará, legal demands varied depending on the year and the characteristics of health care, with the IDH-M variable being significantly associated with the type of legal demand between 2010 and 2018.